Paleontologia dos Discinidae (Brachiopoda: Linguliformea) da sucessão devoniana da Bacia do Paraná, Estado do Paraná, Brasil: Revisão sistemática, distribuição geográfica e estratigráfica. - Comniskey, Jeanninny Carla (2011)
The present paper is about branchiopods discinids that occur from the Devonian succession in the state of Paraná, Brazil. The following themes were discussed: systematic review, basic taphonomic analysis and a geographic distribution and stratigraphic. The fieldworks were developed with the intuition of collecting material with stratigraphic control. It was recorded four species of discinids: Orbiculoidea baini, Orbiculoidea bodenbenderi, Orbiculoidea excentrica e Gigadiscina collis. The discinids occur from the Neopraguiano until at least Eogivetiano. The stratigraphic and geographic distribution varies with the species. Considering about the extinction of the group, along with its collapse of the malvinokaffric fauna is also presented. The transference from Orbiculoidea collis taxon to Gigadiscina collis and its maintenance of the others species with originals descriptions added to new data are also presented.